Zeta-Fe2O3--A new stable polymorph in iron(III) oxide family - Tuček, Jiří; Machala, Libor; Ono, Shigeaki; Namai, Asuka; Yoshikiyo, Marie; Imoto, Kenta; Tokoro, Hiroko; Ohkoshi, Shin-ichi; Zbořil, Radek (Scientific reports, 2015)
Iron(III) oxide shows a polymorphism, characteristic of existence of phases with the same chemical composition but distinct crystal structures and, hence, physical properties. Four crystalline phases of iron(III) oxide have previously been identified: α-Fe2O3 (hematite), β-Fe2O3, γ-Fe2O3 (maghemite), and ε-Fe2O3. All four iron(III) oxide phases easily undergo various phase transformations in response to heating or pressure treatment, usually forming hexagonal α-Fe2O3, which is the most thermodynamically stable Fe2O3 polymorph under ambient conditions. Here, from synchrotron X-ray diffraction experiments, we report the formation of a new iron(III) oxide polymorph that we have termed ζ-Fe2O3 and which evolved during pressure treatment of cubic β-Fe2O3 (Ia3 space group) at pressures above 30 GPa. Importantly, ζ-Fe2O3 is maintained after pressure release and represents the first monoclinic Fe2O3 polymorph (I2/a space group) that is stable at atmospheric pressure and room temperature. ζ-Fe2O3 behaves as an antiferromagnet with a Néel transition temperature of ~69 K. The complex mechanism of pressure-induced transformation of β-Fe2O3, involving also the formation of Rh2O3-II-type Fe2O3 and post-perovskite-Fe2O3 structure, is suggested and discussed with respect to a bimodal size distribution of precursor nanoparticles.